Importance of perceived adulthood and goal pursuit in emerging adult college students - Rarick, Timothy Michael (Kansas State University, 2011)
Previous research has discovered that most 18-to-25 year olds do not feel they have reached the rite of passage known as adulthood. This period of development, termed “emerging adulthood”, is characterized by identity exploration and myriad possibilities related to who one is and what one wants out of life. Empirical evidence suggests that future goals linked to one’s identity are more likely to be obtained through three actions specified in the Selection-Optimization-Compensation (S.O.C.) model: selecting goals to focus one’s resources, optimizing goal-relevant means, and, when necessary, compensating for losses that may occur in these means. The purpose of this study was (a) to identify the proportions of 18-to-25 year old perceived adults vs. emerging adults in a university sample (n = 828); (b) to assess the degree to which self-reported perceived adult status distinguishes self-reports of achieved adult criteria, goal-pursuit strategies, and subjective well-being, and; (c) to determine the predictive utility of perceived adult status, background characteristics, and goal-pursuit strategies for understanding individual differences in life satisfaction, positive affect (i.e., subjective vitality), and negative affect (i.e., depressive symptoms). Analyses of on-line survey responses indicated that approximately one-fourth (24%) of participants reported they had reached adulthood, and, compared to their emerging adult peers, had achieved more criteria for adulthood and were using more effective goal-pursuit strategies. Step-wise multiple regression analyses revealed that specific background characteristics (e.g., relationship status and GPA) and goal-pursuit strategies (e.g., optimization) were significant and strongest predictors of the participants’ life satisfaction, positive affect, and negative affect. Perceived adult status was a significant moderate predictor of both life satisfaction and positive affect but was unrelated to negative affect. Implications of the findings for developmental researchers, educators, and practitioners are discussed.
Keywords: Emerging adulthood; Higher education; Goal pursuit; Subjective well-being; Identity development; Adulthood; Behavioral Sciences (0602); Developmental Psychology (0620); Education, General (0515); Higher Education (0745); Individual & Family Studies (0628); Psychology (0621)